ANALYZING THE PRODUCT POSITIONING OF WOMEN’S BEAUTY SOAP IN MANADO - Asinda, Septian D.C. (FEB Universitas Sam Ratulangi Manado, 2013)
There is no product in the world that does not have a position. Product position is the position of a product relative to competing products in the minds of customers. One way to assess the current position of a product relative to competitors is to compare the various product on some physical characteristics (size, weight etc.). The objective of this research is to know the product positioning of women’s beauty soap in Manado. This research uses descriptive type of research where it will investigate the product positioning of women beauty soap in Manado and the effect of the products to Manado’s women perception. The population in this research is the female students who are using beauty products in the environment of International Business Administration Program, Faculty of Economics and Business, Unsrat Manado. Samples taken are 40 respondents. The conclusion are: first Lux and Lervia brand percepting by respondents having similarity; second don’t have similarity perception of respondents; third Shinsui and Skin White have similar perception of the respondents, and the final one is Dove don’t have similarity with other brand of woman’s beauty soap products. Keywords: product positioning, beauty soap